Pengaruh Pajak Daerah, Retribusi Daerah, Hasil Pengelolaan Kekayaan Daerah Yang Dipisahkan Dan Pendapatan Asli Daerah Lainnya yang Sah Terhadap Pendapatan Asli Daerah (PAD) Di Kabupaten Lembata Provinsi Nusa Tenggara Timur - St. Miftahurrizqa Miftah; Ansar Taufiq; Yusram Adi (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2026)
This study aims to analyze the effect of Regional Taxes, Regional Retributions, Separated Regional Wealth Management Results, and Other Legitimate Regional Original Revenues on the Regional Original Revenue (PAD) of Lembata Regency for the 2020–2024 period. The research employs a quantitative approach with an associative and causal-comparative design, using secondary data obtained from the Regional Budget Realization Reports (APBD), official government documents, and publications from the BPS. The sampling technique used is the census (saturated sampling) method with a total of 60 observational units, and data analysis was conducted using multiple linear regression. The results show that partially, Regional Retributions and Other Legitimate PAD have a positive and significant effect on the PAD of Lembata Regency. Meanwhile, Regional Taxes and Separated Regional Wealth Management Results (HPKDD) have a positive but insignificant effect. Simultaneously, the four independent variables have a significant effect on PAD. These findings indicate that the management of retributions and other legitimate revenues plays a dominant role in enhancing regional fiscal independence, while the contribution of regional taxes and HPKDD still needs to be optimized through improved governance, tax policy effectiveness, and the performance of regional-owned enterprises (BUMD) to strengthen the regional financial structure sustainably.